Best nonsurgical managements of acute urinary retention: what's new?. Issue 2 (March 2022) - Baboudjian, Michael; Peyronnet, Benoit; Boissier, Romain; Robert, Grégoire; Cornu, Jean-Nicolas; Misrai, Vincent; Pradere, Benjamin
Abstract : Purpose of review: To provide a comprehensive review of the nonsurgical management of acute urinary retention (AUR). Recent findings: A recent meta-analysis confirmed that α-blockers are associated with higher rates of successful trial without catheter (TWOC) compared with placebo, while combination therapies do not significantly reduce the rate of recatheterization. Compared with standard TWOC, bladder perfusion with physiological serum prior to catheter removal is a simple and cost-effective method to increase TWOC success rates (odds ratio 2.41, 95% confidence interval 1.53–3.8), and to reduce time-to-discharge (−89.68 min, 95% confidence interval −160.55, −18.88). Clean intermittent catheterization (CIC) is increasingly used for urinary retention in patients with benign prostatic hyperplasia as existing data suggest that it may decrease the risk of urinary tract infections, accelerate spontaneous voiding recovery and might be more cost-effective compared with indwelling urethral catheterization. Ongoing trials are examining whether office-placed prostate stent may be a promising solution in patients with AUR. Summary: The recent development of alternative approaches to traditional TWOC may lead to new therapies for treating patients with AUR. Further studies are needed as the level of evidence from published studies remains low.